Accuracy of optical coherence tomography imaging in assessing aneurysmal remnants after flow diversion. (2nd June 2020) - Fries, Frederik; Maßmann, Alexander; Tomori, Toshiki; Yilmaz, Umut; Kettner, Michael; Simgen, Andreas; Cattaneo, Giorgio; Wagenpfeil, Gudrun; Reith, Wolfgang; Mühl-Benninghaus, Ruben
Abstract : Background: Optical coherence tomography (OCT) is an ultra-high resolution real-time intravascular imaging method that is gaining interest in cerebrovascular applications. Objective: To compare, in a rabbit elastase aneurysm model, digital subtraction angiography (DSA) and OCT as diagnostic tools for the assessment of aneurysmal remnants and baseline characteristics of aneurysms after flow diverter (FD) implantation. Methods: With Institutional Animal Care and Use Committee approval, saccular aneurysms were created in 28 rabbits and treated with Derivo FDs. DSA was performed before, and immediately after, stent implantation. As a follow-up, DSA and OCT were performed 28 days after device implantation. Results: DSA and OCT were successfully performed in 23 cases. OCT could not be achieved in 5 cases owing to navigational difficulties in the stent lumen with the OCT catheter. Residual aneurysms were significantly more often visible with OCT (18/23 (78%) than with DSA 12/23 (52%), p = 0.031). Conclusion: OCT was more sensitive than conventional angiography for the assessment of residual aneurysms at 28 days after FD implantation in an animal model.